Study of Exhaled Nitric Oxide in Subjects with Suspected Obstructive Sleep Apnea: A Pilot Study in Vietnam - Sy Duong-Quy; Thong Hua-Huy; Huyen-Tran Tran-Mai-Thi; Nhat-Nam Le-Dong; Timothy J. Craig; Anh-Tuan Dinh-Xuan (Pulmonary Medicine)
Background and Objective. The concentration of exhaled nitric oxide (eNO), reflecting the activity of inducible NO synthase in airway epithelium, has been found to increase in patients with obstructive sleep apnea (OSA). This study aimed to measure eNO concentration in patients with suspected OSA and to correlate different eNO parameters with clinical and sleep apnea characteristics. Methods. In this cross-sectional study, all patients underwent in-lab overnight polysomnography (PSG) and eNO measurement using a method of multiple flow rates before and after PSG (pre- and post-PSG). Results. According to the result of PSG, 82 persons were divided into two groups: control subjects (n=30; 54±14 years) and patients with OSA defined as apnea-hypopnea index (AHI) ≥ 5/hour (n=52; 53±12 years). Body mass index (BMI) and neck and abdomen circumferences of OSA patients were significantly higher than those from control subjects. In OSA group, post-PSG alveolar NO concentration (CANO) (5.3±1.9 ppb) was significantly higher than pre-PSG CANO (4.0±1.7 ppb; P<0.001). Significant correlations have been found between CANO and AHI (P<0.001) and between CANO and nadir SpO2 (P<0.05). The daytime CANO value of more than 4.1 ppb can be used to screen symptomatic subjects for the presence of OSA with a high specificity of 93.3%. Conclusion. Our findings indicate CANO as a surrogate marker for OSA in persons with suggestive symptoms.